Soil Mesofauna Community on Ex-Landfills Land Gunung Tugel Banyumas Regency - Susanto Susanto; Erin Putri Latifatul Briliani; Cahyono Purbomartono (UM Purwokerto Press, 2022)
This study aims to identify and reveal the soil fauna community which includes individual counts, diversity and dominance as well as the quality of the soil environment in the former landfills Gunung Tugel land, Kedung Randu Village, Patikraja District, Banyumas Regency. The method used is purposive random sampling. Sampling was carried out for six months, during January-June 2021, six times with an interval of one month, at day (06.00 - 08.00) and night (18.00-20.00). Soil sampling and soil quality measurements were carried out at two research locations, location I in the northern and eastern areas of the ex-landfills Gunung Tugel area and location II in the western and southern areas of the ex- landfills Gunung Tugel area. The results of the sampling were identified using a microscope and referred to the book An Introduction to the Study of Insects and the book Ecology of Soil Animals. The results showed that 394 individuals of soil mesofauna were counted which belonged to 12 orders, 15 families and 17 species. The diversity index is classified as moderate, in the range of 0.970 - 1.097 with an average of 1.045. The dominance index is relatively low, ranging from 0.335 to 0.423 with an average of 0.367 and shows that no species dominates. The quality of the soil environment of the former Gunung Tugel landfills is classified as not yet feasible to support the life of the soil mesofauna.